Volatile Organic Compounds of Streptomyces sp. TOR3209 Stimulated Tobacco Growth by Up-Regulating the Expression of Genes Related to Plant Growth and Development - He, Yuxi; Guo, Wenyu; Peng, Jieli; Guo, Jinying; Ma, Jia; Wang, Xu; Zhang, Cuimian; Jia, Nan; Wang, Entao; Hu, Dong; Wang, Zhanwu (Frontiers in Microbiology, 2022)
To investigate the mechanism underlying the plant growth-promoting (PGP) effects of strain Streptomyces sp. TOR3209, PGP traits responsible for indoleacetic acid production, siderophore production, and phosphate solubilization were tested by culturing the strain TOR3209 in the corresponding media. The effects of volatile organic compounds (VOCs) produced by the strain TOR3209 on plant growth were observed by co-culturing this strain with tobacco seedlings in I-plates. Meanwhile, the effects of VOCs on tobacco gene expression were estimated by performing a transcriptome analysis, and VOCs were identified by the solid-phase micro-extraction (SPME) method. The results showed positive reactions for the three tested PGP traits in the culture of strain TOR3209, while the tobacco seedlings co-cultured with strain TOR3209 revealed an increase in the fresh weight by up to 100% when compared to that of the control plants, demonstrating that the production VOCs was also a PGP trait. In transcriptome analysis, plants co-cultured with strain TOR3209 presented the highest up-regulated expression of the genes involved in plant growth and development processes, implying that the bacterial VOCs played a role as a regulator of plant gene expression. Among the VOCs produced by the strain TOR3209, two antifungal molecules, 2,4-bis(1,1-dimethylethyl)-phenol and hexanedioic acid dibutyl ester, were found as the main compounds. Conclusively, up-regulation in the expression of growth- and development-related genes via VOCs production is an important PGP mechanism in strain TOR3209. Further efforts to explore the effective VOCs and investigate the effects of the two main VOCs in the future are recommended.